Prevalence of von willebrand disease in dogs from São Paulo State, Brazil - Mattoso, Cláudio Roberto S. [UNESP]; Takahira, Regina Kiomi [UNESP]; Beier, Suzane Lílian; Araújo Jr., João Pessoa [UNESP]; Corrente, José Eduardo [UNESP] (SAGE Publications, 2010)
The aims of the current study were to assess the prevalence of von Willebrand disease (vWD) in dogs from the region of Botucatu, São Paulo State, Brazil, and to evaluate laboratory tests to diagnose this disease. The study included 350 dogs of various ages, different breeds, and both sexes. Dogs included in the study had no historical or clinical evidence of abnormal bleeding. von Willebrand factor antigen (vWF:Ag), buccal mucosal bleeding time, activated partial thromboplastin time, and factor VIII activity were evaluated in their ability to diagnose vWD. The prevalence of vWD in dogs was 1.43% in the Botucatu region of Brazil. Determination of vWF:Ag was the best laboratory test to diagnose vWD.
Keywords: Brazil; Dogs; Von willebrand disease